Pengaruh Kompetensi dan Pelatihan Terhadap Kinerja Karyawan PT. Sago Nauli Group Kabupaten Mandailing Natal - Yusnita Helvy; Muhammad Ichsan Hadjri; Zunaidah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of the study is to determine the effect of competence and training on employees performance at PT. Sago Nauli Group Kabupaten Mandailing Natal. The sample taken with slovin formula which are 71 employees from every division. The data obtained by distruiting questionnaires to respondents. The method used is data analysis technique using multiple linear regression analysis. The results show that competence has a positive and significant effect on employees performance, training has a positive and significant effect on employees performance, and competence and training together have a positive and significant effect on employees performance.